The Influence of Corporate Social Responsibility, Accounting Conservatism, Audit Committee, Capital Structure, and Dividend Policy on Firm Value - Dwi Putri Maulida; Anies Indah Hariyanti (International Forum of Researchers and Lecturers, 2025)
The behind of this study motivated from the importance of company value in sustaining the company’s operation and enhancing its competitiveness. The purpose of this research was to identify and analyze the partially impact of corporate social responsibility (CSR), accounting conservatism, audit committee, capital structure, and dividend policy on firm value, as measured by Tobin’s Q, in manufacturing companies within the consumer goods industry sector listed on the Indonesia Stock Exchange from 2021 to 2023. The technique of data sampling using purposive sampling method. Resulting in data from 20 companies, comprising 60 financial statements and annual reports that met the representative criteria. The research employed descriptive statistical analysis, panel data regression analysis, estimation technique selection for panel data regression, classical assumption tests, and hypothesis testing. The findings revealed that the CSR variable did not have a significant positive effect on firm value, the accounting conservatism variable had a significant positive effect, the audit committee variable exhibited a significant negative effect, the capital structure variable demonstrated a significant positive effect, while the dividend policy variable did not have a significant positive effect on firm value.